Effects of Huang-Lian-Jie-Du decoction on improving skin barrier function and modulating T helper cell differentiation in 1-chloro-2,4-dinitrobenzene-induced atopic dermatitis mice - Zhang, Huiyuan; Li, Quanbin; Li, Yaxing; Guan, Jianhua; Li, Kaidi; Chen, Yunlong (Frontiers in Pharmacology, 2024)
Background: Atopic dermatitis (AD) is among the most frequently encountered skin diseases, bothering a considerable number of patients. Today, corticosteroids and antihistamines are among the numerous drugs applied for the therapy of AD. However, lengthy use of them contributes to side effects, such as physiological changes in skin. As an alternative and supplementary therapy, traditional Chinese medicine has become a trend for AD treatment. Huang-Lian-Jie-Du Decoction (HLJDD), a renowned herbal formula has been employed to treat inflammatory diseases such as AD. However, its role in regulating immunity in AD remains unclear. The object of this study was to elucidate the efficacy of HLJDD and reveal the implicit mechanism from an immunological perspective in AD-like mice.Methods: In brief, 1-chloro-2,4-dinitrobenzene (DNCB) for the sensitization phase (1% DNCB) and stimulation phase (1.5% DNCB) were applied for BALB/c mice. HLJDD and dexamethasone (DXMS) were administered orally to the mice. Mice skin and spleens were collected to evaluate the efficacy of HLJDD. 16S rRNA sequencing was applied to evaluate the commensal microbiota changes in skin and fecal. In vitro, spleen CD4 + T cells and bone marrow-derived mast cells (BMMCs) were co-cultured to explore the modulation of HLJDD in T helper (Th) cells phenotyping. Results: HLJDD showcased a substantial amelioration in skin through the up-regulation of FLG, LOR, AQP3, and reducing scratching behaviors in AD-like mice, Also, the quantity of infiltrated mast cells (MCs), pruritus-related mRNA were decreased. In addition, the expression of OX40/OX40L was decreased by HLJDD, which was critical in Th-cell phenotyping. With the treatment of HLJDD, Th1/Th2 and Th17/Treg ratios in AD-like mice became balanced. The structure of commensal microbiota in AD-like mice was affected by HLJDD. HLJDD could also improve the imbalance of Th17/Treg in vitro.Conclusion: HLJDD could improve the symptoms of AD-like mice by alleviating the scratching behaviors via decreased Th2 and pruritus-related mRNA expression. HLJDD also enhanced the relative diversity of skin microbiota and changed the structure of intestinal microbiota. An in-depth study found that HLJDD could balance the ratio of Th1/Th2, Th17/Treg in AD-like mice, and Th17/Treg in vitro by regulating the OX40/OX40L signaling pathway.